The Evaluation of Didactic Quality the Textbooks of Civics - Vyškovská, Zuzana (Civilia, 2013)
This paper deals with the evaluation of didactic quality the textbooks of civics for primary schools and Gymnasiums. Author evaluated two series of textbooks - textbooks from Nakladatelství Fraus and Nová škola.
Keywords: Didactic quality the textbooks; Textbooks of civics; Text difficulty